The Routledge companion to modern Christian thought - Meister, Chad 1965-; Beilby, James K.; Meister, Chad 1965- (London [u.a.] Routledge, Taylor & Francis Group, 2013)
"This Companion provides an unrivalled view of the field of modern Christian thought, from the Enlightenment to the twentieth century and beyond. Written by an outstanding team of theologians and philosophers of religion, it covers the following topics: - Key figures and influencers - Central events and movements - Major theological issues and key approaches to Christian Theology - Recent topics and trends in Christian thought Each entry is clear and accessible, making the book the ideal resource for students of Christian thought and the history and philosophy of religion. It is also a valuable reference for professional theologians and philosophers"--
Includes bibliographical references and index
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Theology, Doctrinal -- History -- Modern period, 1500-; Theology, Doctrinal -- History -- 21st century; Aufsatzsammlung